Renormalization of Newton's constant - Falls, Kevin (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
The problem of obtaining a gauge independent beta function for Newton’s constant is addressed. By a specific parametrization of metric fluctuations a gauge independent functional integral is constructed for the semiclassical theory around an arbitrary Einstein space. The effective action then has the property that only physical polarizations of the graviton contribute, while all other modes cancel with the functional measure. We are then able to compute a gauge independent beta function for Newton’s constant in d dimensions to one-loop order. No Landau pole is present provided Ng<18, where Ng=d(d−3)/2 is the number of polarizations of the graviton. While adding a large number of matter fields can change this picture, the absence of a pole persists for the particle content of the standard model in four spacetime dimensions.